Role of Tricuspid Valve Repair for Moderate Tricuspid Regurgitation during Minimally Invasive Mitral Valve Surgery - Pfannmueller, Bettina; Verevkin, Alexander; Borger, Michael Andrew; Mende, Meinhard; Davierwala, Piroze; Garbade, Jens; Mohr, Friedrich Wilhelm; Misfeld, Martin (The Thoracic and Cardiovascular Surgeon, 2013)
Background The aim of this study was to investigate the impact of short- and mid-term survival of tricuspid valve (TV) repair versus conservative therapy in patients with preoperative moderate functional tricuspid regurgitation (TR) undergoing minimally invasive mitral valve (MV) surgery.Methods Between January 2002 and December 2009, a total of 430 patients with pure mitral regurgitation and concomitant moderate TR underwent minimally invasive MV surgery for mitral regurgitation at the Leipzig Heart Center without (n = 336; group A) and with (n = 94; group B) TV surgery. Mean age was 66.7 ± 10.3 years, mean LVEF was 58.0 ± 13.8%, and 206 patients (47.9%) were male. Average logEuroSCORE was 12.4 ± 11.4%. Follow-up was on average 4.6 ± 2.4 years and 97% completed.Results Predischarge echocardiography showed no or mild TR in 51.1% of patients in group A versus 84.2% of patients in group B (p < 0.01). Overall 30-day mortality was 2.8% with no differences between both groups. Five-year survival was 82.9 ± 4.1% for patients with TV repair versus 85.0 ± 2.2% for patients without TV repair (p = 0.1) and it was 85.7 ± 3.3% in patients with moderate and more postoperative TR versus 90.1 ± 2.5% in patients with less than moderate postoperative TR (p = 0.08). Five-year freedom from TV-related reoperation was 98.8 ± 0.7% for patients in group A versus 98.9 ± 0.1% for patients in group B (p = 0.8).Conclusions Patients undergoing MV surgery with moderate functional TR do not experience increased perioperative complication rates when a concomitant TV repair is performed. Our observations, combined with those of other groups, support current recommendations to perform concomitant TV repair in such patients, particularly if tricuspid annular dilation is present.
Keywords: tricuspid valve; mitral valve surgery; minimally invasive surgery